Assessing the utility of selected photosynthetic and related traits in screening Amaranthus dubius Mart. ex Thell. and Galinsoga parviflora Cav. 1796 seedlings for elevated temperature stress tolerance - Areington, Candyce Ann; Lima Neto, Milton Costa [UNESP]; Watt, Paula M.; Sershen (My University, 2022)
Wild leafy vegetables are of increasing interest because many have higher concentrations of some beneficial minerals, vitamins and nutrients than commercial crops. Some reports also indicate that they exhibit high levels of tolerance to abiotic stressors associated with climate change. The aim of this study was to investigate whether selected biochemical, physiological (related to photosynthesis) and morphological traits could be used to screen for elevated temperature tolerance in two wild leafy vegetable species, viz. Amaranthus dubius (C4) and Galinsoga parviflora (C3). One-month-old seedlings were transferred from a greenhouse to growth chambers and subjected to either ambient [25°C (day)/14°C (night)] or elevated [30°C (day)/19°C (night)] temperatures for 15 days. On days 0, 5, 10 and 15, gas exchange, chlorophyll fluorescence, selected biochemical, physiological and morphological traits were determined. Data for the 24 traits measured were used in plant trait network analyses to establish the populations’ phenotypic plasticity, including changes in the interactions/relationships amongst the traits when exposed to elevated temperatures. Sixteen traits showed significant differences between ambient and elevated temperatures on day 15, 11 in G. parviflora only, one in A. dubius only and four in both species. Those shared by the two species were intracellular hydrogen peroxide, electrolyte leakage, ascorbate peroxidase, and superoxide dismutase, while specific leaf area was significantly different in A. dubius only. Both species altered biochemical leaf traits under elevated temperatures, while morphological leaf traits were altered in A. dubius only and photosynthetic leaf traits in G. parviflora only. In G. parviflora, the photosynthetic traits were more sensitive to elevated temperatures than in A. dubius. This suggests that photosynthetic traits may be ineffective for screening C4 species, due to them being highly evolved to survive in warmer climates. However, the results showed that photosynthetic traits could be useful as screening tools for C3 photosynthetic pathway species. The plant trait network analyses showed that both species displayed high phenotypic plasticity with a 5°C increase in temperature. We recommend when screening wild leafy vegetables for high temperature tolerance that photosynthetic traits be considered in the context of their phenotypic plasticity. This approach could fast-track the identification of more climate-resilient wild edible species.
Keywords: Amaranthus dubius; elevated temperature tolerance; Galinsoga parviflora; phenotypic plasticity; photosynthetic traits; plant trait networks